Full-solution processed all-nanowire flexible and transparent ultraviolet photodetectors. Issue 43 (24th October 2018) - Li, Yi; Li, Yinghui; Chen, Jun; Sun, Zhipeng; Li, Zhuang; Han, Xiao; Li, Pan; Lin, Xiujing; Liu, Ruiqing; Ma, Yanwen; Huang, Wei
Abstract : Full-solution processed all-nanowire flexible and transparent UV photodetectors based on a Ag NW/ZnO NW/Ag NW sandwich MSM structure are successfully fabricated and exhibit low operation voltage, excellent photoresponse properties, high transparency and superior mechanical stability. Abstract : Sandwich metal–semiconductor–metal (MSM) structured ultraviolet (UV) photodetectors have attracted much attention in wearable and implantable electronics due to their large UV adsorption area and high compatibility for large-scale production. However, there is a lack of an effective approach to fabricate highly transparent and flexible sandwich MSM structured devices. In this work, we develop a full-solution process to fabricate a flexible and transparent sandwich MSM structured device based on vertically aligned zinc oxide nanowires (ZnO NW) arrays. To achieve high flexibility and transparency, silver nanowires (Ag NW) networks were introduced as both bottom and top electrodes, and especially as substrates for vertically aligned ZnO NW array growth. Such a Ag NW/ZnO NW/Ag NW sandwich MSM structured device shows a high transparency of 75.0% and excellent mechanical stability. This UV photodetector exhibits a low operation voltage of 0.5 V, a high photocurrent/dark current ratio of 9756 and fast photoresponse properties with a rise time of 1.83 s and a decay time of 1.75 s, demonstrating great potential for low cost and large area wearable electronics applications.